Intergenerational Equity and Sustainability in Korea: Toward Participatory Policy Governance - Hisam Kim; Soonhee Kim (Korea Development Institute (KDI), 2016)
Cases of policy decision-making processes that fail to fully recognize the foreseeable problems facing younger and future generations indicate that current policy governance is vulnerable in terms of intergenerational equity and sustainability. Hence, it is vital to design an effective policy governance system for resolving intergenerational problems; one in which policymakers can consider the long-term impact of their decisions not only on different living generations but also on future generations. To fulfill this task, a participatory policy governance system has been proposed as a way of promoting the input from different generations, and on behalf of future generations in policy decision-making processes in the legislative and administrative sectors. Creating a civic culture for future responsibility at the community level should be also emphasized. Institutionalizing the participatory policy governance system and the culture for future responsibility could help to alleviate increasing generational conflict in Korea during the coming era of slow growth and aging population. - Generational conflicts are increasingly likely to grow stronger in the policy decision-making process as well as in voting. - Indeed, some policy cases even failed to take into account of the fully expected problems and are simply centered on present generations. - Most respondents in all age groups agree on the need for an institutional mechanism that could strengthen younger people's political influence. - Positive responses to the willingness for intergenerational communication and discussion outnumber the negative responses, while 20s remain laid-back. - Efforts to seek intergenerational equity and sustainability encounter challenges such as deepening generational heterogeneity resulting from rapid changes in Korean history, rapid aging of the population, weak social trust, and poor capacity to resolve conflicts. - Efforts are needed to appoint representatives of younger and future generations to the National Assembly through the proportional representation system, to establish a permanent committee for future generations, and to lower the voting age. - Other efforts include establishing a presidential committee for future generations, creating a system of participatory budgeting that includes young people and adolescents, gathering public opinion through direct democratic methods, and enhancing access to policy information. - Improving civic awareness and capabilities through civic movements could serve as a basis for pursuing broader participation, deliberation, and consensus building in governance.
Keywords: 330